Identifikasi Gaya Belajar Anak Usia Dini - Maulinda Sulistyani Sanjaya; Dessy Farantika; Devi Candra (Universitas Islam Tribakti Lirboyo Kediri, 2023)
A way that each individual carries out receiving lessons and information from the environment is a form of learning style. This study intends to examine how early childhood learning. This study used a descriptive research method; the research subject was Dharma Wanita Jimbe 1 Kindergarten, Blitar Regency, with 13 students in 2022/2023. Data collection was carried out using observation and interviews. The results of this study illustrate that children have characteristics in understandingand learning something different from adults. Playing while learning is an activity carried outby an early childhood with feelings of pleasure, without coercion, but has patterns that are expected to create good growth and development for children. Playing while learning in early childhood has goals that adults may not realize, whereas when a childplays, he is actually developing the potential in him. Developing children's skills from an early age helps build children's rational thinking processes; children are also better prepared to face life's problems in the future. This research is expected tobe a reference and knowledge for parents and teachers, especially to understand the world of early childhood, one of which is by understanding the nature of learning and the meaning of learning styles for early childhood.